When Concursus Realis Fails: Voortgezette Handeling for Sexual Abuse Against Male Children at Pesantren - Filda Rosa; Edi Rosman (Hakamain: Journal of Sharia and Law Studies, 2026)
This study aims to examine the legal qualification of repeated sexual abuse against male children in pesantren (Islamic boarding schools) by evaluating the application of concursus realis and voortgezette handeling under Indonesian criminal law from the perspective of Islamic law. This study employed an empirical legal method with a qualitative approach through field research conducted from January to March 2026. Data were collected through semi-structured interviews with judges, public prosecutors, investigators, advocates, criminal law scholars, and Islamic law scholars, supported by observations and document analysis. Documentary sources included the Indonesian Criminal Code, Law Number 12 of 2022 on Sexual Violence Crimes, Decision Number 130/Pid.Sus/2024/PN Bukittinggi, Decision Number 989/Pid.Sus/2021/PN Bandung, and related legal documents. The findings indicate that judicial practice predominantly applies concursus realis, emphasizing the plurality of criminal acts while overlooking the continuity of criminal intent and the cumulative harm suffered by child victims. Interview participants considered voortgezette handeling a more appropriate legal framework because it recognizes repeated offenses arising from a single criminal intent, thereby supporting proportional punishment, consistent judicial reasoning, and stronger child protection. This study concludes that reconstructing the application of voortgezette handeling is necessary to strengthen legal certainty, sentencing consistency, and victim protection. Academically, this study contributes an empirical and doctrinal framework integrating Indonesian criminal law with Islamic legal principles to improve judicial responses to continuing child sexual abuse cases.